2020
DOI: 10.1177/0033294120984127
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Overview of Meta-Analyses on Socioeconomic Status, Cognitive Ability, and Achievement: The Need to Focus on Specific Pathways

Abstract: Meta-analyses on the relation between socioeconomic status (SES) and performance on measures of cognitive ability and achievement arrive at the same general conclusion of a small to medium association. Advancements in methods make possible for meta-analyses to examine specific pathways linking SES to cognitive ability and achievement, as well as the moderators of these pathways. In this study, we conducted a systematic overview of meta-analyses on SES to address three research questions: 1) what is the directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 133 publications
(178 reference statements)
1
20
0
Order By: Relevance
“…None of these failed probes overlapped with the probes used for DNA-methylation scores. 44 samples were excluded because (1) they showed low intensity probes as indicated by the log of average methylation <9 and their detection p was > 0.01 in >10% of their probes, (2) their self-reported and methylation-estimated sex mismatch, and/or (3) their self-reported and DNA-estimated sex mismatch. Cell composition of immune and epithelial cell types ( i.e., CD4+ T-cell, natural killer cells, neutrophils, eosinophils, B cells, monocytes, CD8+ T-cell, and granulocytes) were estimated using a newly developed child saliva reference panel implemented in the R package “BeadSorted.Saliva.EPIC” within “ewastools” (22).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…None of these failed probes overlapped with the probes used for DNA-methylation scores. 44 samples were excluded because (1) they showed low intensity probes as indicated by the log of average methylation <9 and their detection p was > 0.01 in >10% of their probes, (2) their self-reported and methylation-estimated sex mismatch, and/or (3) their self-reported and DNA-estimated sex mismatch. Cell composition of immune and epithelial cell types ( i.e., CD4+ T-cell, natural killer cells, neutrophils, eosinophils, B cells, monocytes, CD8+ T-cell, and granulocytes) were estimated using a newly developed child saliva reference panel implemented in the R package “BeadSorted.Saliva.EPIC” within “ewastools” (22).…”
Section: Methodsmentioning
confidence: 99%
“…Six cognitive outcomes were examined in each cognitive model: (1) Processing speed, (2) general executive functions, (3) perceptual reasoning, (4) verbal comprehension, (5) reading, and (6) math.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the many different ways that samples were characterized in terms of education and income in combination with the substantial number of studies where no indicators of socioeconomic status were reported, it was not possible to examine socioeconomic status as a source of heterogeneity. This limitation is not specific to research on familism but also has been documented in other domains of psychological research (Korous et al, 2018(Korous et al, , 2020. In future work, ideally income, educational, and occupational indexes are included to describe the socioeconomic backgrounds of study participants (Cowan et al, 2012;Diemer et al, 2013).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In addition, there is some evidence that non-modifiable factors such socioeconomic status (SES) can influence the brain integrity and cognitive performance (Hackman and Farah, 2009;Hackman et al, 2010;Staff et al, 2012;Zhang et al, 2015;Farah, 2017;Cermakova et al, 2018;Chan et al, 2018;Korous et al, 2020;Steptoe and Zaninotto, 2020;Yaple and Yu, 2020). Although the direct influence of SES on interindividual variability of cognitive outcomes has, to the best of our knowledge, not extensively examined in acute-exercise cognition studies, it is a crucial factor that probably contribute, among other factors, to interindividual variability in a specific neurocognitive outcome parameter and thus should be assessed in future studies investigating interindividual variability.…”
Section: Non-modifiable Factorsmentioning
confidence: 99%